2016
DOI: 10.1179/1743284715y.0000000144
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Zr addition on toughness and microstructure of coarse grained heat affected zone in Al deoxidised low carbon steel

Abstract: The effect of Zr addition on the toughness and microstructure of coarse grained heat affected zone (CGHAZ) in Al deoxidised low carbon steel was investigated. In this present work, the specimens (Zr free and Zr added) were subjected to weld thermal cycle with heat input of 54, 80 and 100 kJ cm 21 at 13508C peak temperature using thermal simulator. The typical inclusions were characterised by scanning electron microscopy, and the chemical composition of the inclusions was determined by energy dispersive spectro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…It was reported that TiN particles precipitated during steel solidification hindered the growth of the austenite grain by pinning at the grain boundary of austenites [7] and inducing the nucleation of Afs [8][9][10][11]. Titanium oxides [12][13][14][15], magnesium oxides [16][17][18], and zirconium oxides [19][20][21][22] in steels owing to the low misfit with ferrites were widely investigated. For example, the formation of the Mn-depletion zone on the surface of Ti 2 O 3 favoured the nucleation of Afs [13], and MgO particles had a low misfit with ferrites which reduced the nucleated energy barrier of Afs [23].…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that TiN particles precipitated during steel solidification hindered the growth of the austenite grain by pinning at the grain boundary of austenites [7] and inducing the nucleation of Afs [8][9][10][11]. Titanium oxides [12][13][14][15], magnesium oxides [16][17][18], and zirconium oxides [19][20][21][22] in steels owing to the low misfit with ferrites were widely investigated. For example, the formation of the Mn-depletion zone on the surface of Ti 2 O 3 favoured the nucleation of Afs [13], and MgO particles had a low misfit with ferrites which reduced the nucleated energy barrier of Afs [23].…”
Section: Introductionmentioning
confidence: 99%